67z=-23

Multiply both sides of the equation by 76.

76⋅67⋅z=76⋅-23

Simplify 76⋅67⋅z.

Cancel the common factor of 7.

Cancel the common factor.

76⋅67⋅z=76⋅-23

Rewrite the expression.

16⋅6⋅z=76⋅-23

16⋅6⋅z=76⋅-23

Cancel the common factor of 6.

Cancel the common factor.

16⋅6⋅z=76⋅-23

Rewrite the expression.

1⋅z=76⋅-23

1⋅z=76⋅-23

Multiply z by 1.

z=76⋅-23

z=76⋅-23

Simplify 76⋅-23.

Cancel the common factor of 2.

Factor 2 out of 6.

z=72(3)⋅-23

Factor 2 out of -2.

z=72⋅3⋅2⋅-13

Cancel the common factor.

z=72⋅3⋅2⋅-13

Rewrite the expression.

z=73⋅-13

z=73⋅-13

Multiply 73 and -13.

z=7⋅-13⋅3

Simplify the expression.

Multiply 7 by -1.

z=-73⋅3

Multiply 3 by 3.

z=-79

Move the negative in front of the fraction.

z=-79

z=-79

z=-79

z=-79

The result can be shown in multiple forms.

Exact Form:

z=-79

Decimal Form:

z=-0.7‾

Solve for z 6/7z=-2/3